Microporous Ceramics Based on β-Tricalcium Phosphate - Tatiana Safronova; Grigorii Grigorev; Tatiana Shatalova; Ilya Roslyakov; Vadim Platonov; Dinara Khayrutdinova (Ceramics, 2022)
Microporous ceramic material, based on β-tricalcium phosphate β-Ca3(PO4)2 with grain size 2–5 μm, pore size smaller than 10 mm, and density 1.22 g/cm3 corresponding to ~40% of the theoretical density (3.07 g/cm3) of β-Ca3(PO4)2, was obtained from a powder mixture with a given molar ratio Ca/P = 1.5 after firing at 1100 °C. A homogenized powder mixture of synthetic dicalcium hydrogen phosphates with the molar ratio Ca/P = 1 and calcium citrate tetrahydrate Ca3(C6H5O7)2·4H2O with the molar ratio Ca/P = ∞ was used for microporous ceramic preparation. The phase composition of calcium phosphate powder, synthesized from an aqueous solution of phosphoric acid H3PO4 and calcium carbonate CaCO3 powder, included brushite CaHPO4·2H2O as the predominant phase. Formation of β-tricalcium phosphate β-Ca3(PO4)2 during firing occurred due to the heterophase interaction of the products of thermal decomposition of the components of the starting powder mixture, namely, calcium pyrophosphate Ca2P2O7 and calcium oxide CaO. The formation of arch-like structures from β-tricalcium phosphate β-Ca3(PO4)2 grains, which were tightly sintered together, hindered the shrinkage of ceramics. The microporous ceramics obtained, based on β-tricalcium phosphate β-Ca3(PO4)2, can be recommended as a biocompatible and biodegradable material for treatment of bone defects and as a substrate for bone-cell cultivation.